Dinamika Ijtihad dalam Lembaga Fatwa Kontemporer: Perspektif Ushul Fikih dan Kontekstualisasi Ijtihad - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study analyzes the dynamics of ijtihad within contemporary fatwa institutions through a comparative ushul al-fiqh framework, emphasizing its role in contextualizing Islamic law. It argues that modern fatwa institutions have transformed ijtihad from an individual to a collective and institutional process, integrating multidisciplinary expertise. While rooted in classical methodologies, these institutions employ maqāṣid al-sharī‘ah to address complex global issues. Comparative insights show a synthesis of madhhab approaches, balancing flexibility and methodological rigor. Despite challenges such as political influence and information overload, fatwa institutions remain crucial mediators between tradition and modernity, ensuring relevant, accountable, and context-sensitive Islamic legal development. Keywords: Ijtihad, Fatwa Institutions, Ushul al-Fiqh